Cálculo de pensiones de jubilación en el Sistema Privado de Pensiones: destapando la caja negra - Bertolotto, Juan (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
The calculation of retirement pensions in the Private Pension System, when tackled by the public media, leaves the wrong impression of being an incomprehensible subject. Certainly it has an important technical component, based in financial estimates and statistics, but starting with common sense elements adequately explained, a sound understanding of the foundations regarding the calculation of retirement pensions could be attained. The aim of this article is, then, to present such foundations and gradually introduce the various technical components in a way that the reader can grasp the fact that calculation of retirements pensions is not the complicated matter it appears to be. For that purpose, we will start with some basic concepts, such as the life and death probabilities that emanate from mortality charts, and the average life expectancy and risk of longevity, so that finally, through examples, pensions from a saved capital can be calculated.

El cálculo de las pensiones de jubilación en el Sistema Privado de Pensiones, cuando es abordado en los medios de información, deja la errada impresión de ser un tema incomprensible. Ciertamente tiene un componente técnico importante, basado en el cálculo financiero y la estadística, pero a partir de elementos propios del sentido común adecuadamente explicados se puede lograr un entendimiento cabal de los fundamentos del cálculo de las pensiones. El objetivo de este artículo es, entonces, presentar dichos fundamentos y paulatinamente introducir los diversos componentes técnicos de manera que el lector comprenda que el cálculo de pensiones resulta menos complicado de lo que aparenta ser. Para ello, empezaremos con algunos conceptos básicos como las probabilidades de vida y de muerte que emanan de las tablas de mortalidad, y la esperanza media de vida y el riesgo de longevidad, para finalmente, mediante ejemplos, calcular pensiones a partir de un capital ahorrado.
Calculation of retirement pensions in the Private Pension System: uncovering the black box
Keywords: Pensión de jubilación; Tabla de mortalidad; Probabilidad de muerte; Esperanza media de vida; Riesgo de longevidad; Capital requerido unitario; https://purl.org/pe-repo/ocde/ford#5.02.04